(untitled) (Scottish Historical and Archaeological Internet Reports, 2011)
The finds assemblage was almost entirely of medieval date, but for a handful of post-medieval and modern finds. The ditch provided the best of the assemblage. Other finds were from garden soils and were considerably more abraded. Waterlogging led to some good preservation of organic materials and metals, unusual in Edinburgh, including leather footwear, a wooden barrel and a horn comb. The finds assemblage represents a selection of the belongings and tools of the people who lived and worked along the Cowgate and upslope along the High Street during the medieval period, particularly during the 15th century. There are specialist reports on pottery, coins, copper alloy, lead, iron, bottle and window glass, ceramic building material, leather and a coopered vessel. These are followed by a phase discussion.